Positive electrode active material and lithium secondary battery including the same
Patent Information
- Application Number
- CN202180042126.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-12
- Filing Date
- 2021-06-11
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-06-11
AI Technical Summary
然而,虽然这种高镍正极活性物质示出高容量特性,但存在随着正极活性物质中的Ni含量增加而导致由Li/Ni阳离子混合引起的结构不稳定的问题
[0038]构成根据本发明的正极活性物质的锂复合氧化物与具有大致为球形的表面部的现有锂复合氧化物不同地,在表面部具有台阶结构,上述台阶结构可以在使上述锂复合氧化物的结构稳定的同时抑制与电解液的副反应。
Smart Images

Figure CN115699362B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a positive electrode active material for lithium secondary batteries and a lithium secondary battery including the same, which improves the electrochemical characteristics and stability that are in a trade-off relationship by introducing a step structure into the surface of the lithium composite oxide constituting the positive electrode active material. Background Technology
[0002] Batteries use materials capable of electrochemical reactions at the positive and negative electrodes to store electrical energy. As a representative example of such batteries, there are lithium-ion secondary batteries that store electrical energy through the difference in chemical potential during the insertion / extraction of lithium ions at the positive and negative electrodes.
[0003] The aforementioned lithium secondary battery is prepared by using materials capable of reversible lithium-ion insertion / extraction as positive and negative electrode active materials, and filling the space between the positive and negative electrodes with organic or polymer electrolytes.
[0004] Representative materials used as positive electrode active materials in lithium secondary batteries include lithium composite oxides. Examples of such lithium composite oxides include LiCoO2, LiMn2O4, LiNiO2, LiMnO2, or oxides of Ni, Co, Mn, or Al complexes as disclosed in Korean Patent Publication No. 10-2015-0069334 (publication date: June 23, 2015).
[0005] Among the aforementioned positive electrode active materials, LiCoO2 is the most widely used due to its excellent lifetime characteristics and charge / discharge efficiency. However, due to the limited resources of cobalt as a raw material, its price is expensive, thus limiting its price competitiveness.
[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of excellent thermal stability and low price, but they suffer from small capacity and poor high-temperature performance. In addition, LiNiO2-based cathode active materials exhibit high discharge capacity battery characteristics, but they are difficult to synthesize due to the problem of cation mixing between Li and transition metals, resulting in significant problems in rate performance.
[0007] Furthermore, depending on the severity of this cation mixing, a large amount of Li byproducts are generated. Most of these Li byproducts include LiOH and Li₂CO₃, which can lead to gelation during cathode slurry preparation or become a source of gas generation due to repeated charge-discharge cycles after electrode fabrication. In addition, residual Li₂CO₃ in these Li byproducts contributes to reduced lifetime characteristics by increasing monomer swelling.
[0008] To compensate for these shortcomings, the demand for high-nickel (High-Ni) cathode active materials with a Ni content of 50% or more has increased as positive electrode active materials for secondary batteries. However, while these high-nickel cathode active materials exhibit high capacity characteristics, they suffer from structural instability caused by the mixing of Li / Ni cations as the Ni content in the cathode active material increases. Due to the structural instability of the aforementioned cathode active materials, lithium secondary batteries can degrade rapidly not only at high temperatures but also at room temperature.
[0009] Therefore, it is necessary to develop cathode active materials that can overcome the problems of the aforementioned high-nickel cathode active materials. Summary of the Invention
[0010] Technical issues
[0011] In positive electrode active materials for lithium-ion batteries, a predetermined trade-off can be established between indicators representing the electrochemical properties of the positive electrode active material and indicators representing its stability. Therefore, if the capacity characteristics of the positive electrode active material are excessively improved, conversely, the stability of the particles constituting the positive electrode active material deteriorates, potentially resulting in unstable charge-discharge performance.
[0012] Therefore, the object of the present invention is to provide a positive electrode active material that can eliminate low structural stability while maintaining the high electrochemical characteristics of positive electrode active materials for lithium secondary batteries, especially high-nickel positive electrode active materials.
[0013] In particular, the present invention aims to provide a positive electrode active material for lithium secondary batteries that can simultaneously improve the electrochemical properties and stability that are in a trade-off relationship by introducing a step structure into the surface portion of the lithium composite oxide constituting the positive electrode active material.
[0014] Furthermore, another object of the present invention is to provide a lithium secondary battery using a positive electrode comprising a lithium composite oxide as defined herein.
[0015] Solution to the problem
[0016] Previously, a technique was proposed to improve the stability of positive electrode active materials by having light elements, such as boron, exist in the form of oxides, thereby reducing surface side reactions of the positive electrode active materials.
[0017] However, while the aforementioned light elements can reduce side reactions on the surface of the positive electrode active material, they can conversely increase the content of lithium-containing impurities on the surface, depending on their mode of presence, which can lead to a decrease in the electrochemical properties of the positive electrode active material.
[0018] In this context, the inventors discovered that when a stepped structure is introduced into the surface portion of a lithium composite oxide capable of lithium insertion and extraction, electrochemical properties and stability, which have a trade-off relationship, can be improved simultaneously.
[0019] Therefore, according to one aspect of the present invention, a positive electrode active material is provided, wherein the positive electrode active material comprises a lithium composite oxide capable of lithium intercalation and deintercalation, and the lithium composite oxide comprises a surface portion having a stepped structure.
[0020] At this point, the step structure formed on the surface of the aforementioned lithium composite oxide can be a terrace-step-kink structure.
[0021] In one embodiment, the lithium composite oxide is a lithium composite oxide containing at least nickel and cobalt, and may further contain at least one selected from manganese and aluminum.
[0022] Furthermore, the aforementioned lithium composite oxide can be represented by the following chemical formula 1.
[0023] [Chemical Formula 1]
[0024] Li w Ni 1-(x+y+z) Co x M1 y M2 z O2
[0025] (in,
[0026] M1 is at least one selected from Mn and Al.
[0027] M2 is selected from at least one of Mn, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, B, and Cu.
[0028] M1 and M2 are distinct elements.
[0029] 0.5≤w≤1.5, 0≤x≤0.50, 0 <y≤0.20,0≤z≤0.20)
[0030] Furthermore, the aforementioned positive electrode active material includes secondary particles formed by agglomerating multiple of the aforementioned lithium composite oxides as primary particles, and at least a portion of the surfaces of the primary particles and secondary particles may be coated with an oxide containing an oxide represented by the following chemical formula 2.
[0031] [Chemical Formula 2]
[0032] Lia M3 b O c
[0033] (Where M3 is selected from at least one of Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Gd, and Nd, 0≤a≤8, 0 <b≤8,2≤c≤13)
[0034] Even if a coating comprising an oxide represented by the following chemical formula 2 is formed on at least a portion of the surface of the primary and secondary particles, the coating may, like the lithium composite oxide described above, include a surface portion having a stepped structure. Furthermore, the stepped structure formed on the surface portion of the coating may be a platform-stepped bending structure.
[0035] Furthermore, according to another aspect of the present invention, a positive electrode comprising the aforementioned positive electrode active material is provided.
[0036] Furthermore, according to another aspect of the present invention, a lithium secondary battery using the aforementioned positive electrode is provided.
[0037] The effects of the invention
[0038] The lithium composite oxide constituting the positive electrode active material according to the present invention differs from conventional lithium composite oxides having a generally spherical surface portion in that it has a stepped structure on the surface portion, which can stabilize the structure of the lithium composite oxide while suppressing side reactions with the electrolyte.
[0039] In particular, since a coating is formed on the surface of the aforementioned lithium composite oxide, it is possible to suppress the decrease in charge caused by lithium deintercalation and deintercalation, and also to reduce the possibility of side reactions with the electrolyte. Attached Figure Description
[0040] Figure 1 The illustration schematically shows the process of introducing a stepped structure into the surface portion of a lithium composite oxide contained in a positive electrode active material according to an embodiment of the present invention.
[0041] Figure 2 and Figure 3 SEM images of the surface portion of the lithium composite oxide contained in the positive electrode active material according to Example 1 and Comparative Example 1 were taken.
[0042] Figure 4 and Figure 5 SEM images of the surface portion of the lithium composite oxide contained in the positive electrode active material according to Example 3 and Comparative Example 2 were taken respectively.
[0043] Figures 6 to 8 SEM images of the surface of the lithium composite oxide contained in the positive electrode active material of Example 4, Comparative Example 3 and Comparative Example 4 were taken respectively.
[0044] Figures 9 to 11 SEM images of the surface portion of the lithium composite oxide contained in the positive electrode active material according to Example 5, Comparative Example 5 and Comparative Example 6 were taken.
[0045] Figure 12 To capture a TEM image of the surface portion of the lithium composite oxide contained in the positive electrode active material according to Example 1, each crystal facet constituting the surface portion of the lithium composite oxide is shown.
[0046] Figure 13 To illustrate the XPS depth profile of the lithium composite oxide contained in the positive electrode active material according to Example 1, Figure 14 A graph showing the B1s XPS spectra of the regions where boron (B) was detected in XPS depth profiling.
[0047] Figure 15 A diagram showing the interplanar spacing of the crystal planes of regions A and B in a TEM image of the lithium composite oxide contained in the positive electrode active material according to Example 1. Detailed Implementation
[0048] The positive electrode active material according to the present invention and the lithium secondary battery including the thereof will be described in more detail below.
[0049] Positive electrode active material
[0050] According to the present invention, the positive electrode active material on one side is capable of lithium insertion and extraction, and includes a lithium composite oxide comprising a surface portion having a stepped structure.
[0051] The aforementioned lithium composite oxide is a layered oxide comprising at least one transition metal other than lithium, and may include at least nickel and cobalt. Furthermore, in addition to nickel and cobalt, the aforementioned lithium composite oxide may further comprise at least one selected from manganese and aluminum.
[0052] The aforementioned lithium composite oxide can be represented by the following chemical formula 1.
[0053] [Chemical Formula 1]
[0054] Li w Ni 1-(x+y+z) Co x M1 y M2 z O2
[0055] (in,
[0056] M1 is at least one selected from Mn and Al.
[0057] M2 is selected from at least one of Mn, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, B, and Cu.
[0058] M1 and M2 are distinct elements.
[0059] 0.5≤w≤1.5, 0≤x≤0.50, 0 <y≤0.20,0≤z≤0.20)
[0060] As shown in Chemical Formula 1 above, the lithium composite oxide may further include dopants other than nickel, cobalt, manganese, and / or aluminum. In Chemical Formula 1 above, the dopant is represented by M2, where M2 is an element different from M1. That is, when M1 is Mn, M2 is at least one dopant other than Mn; when M1 is Al, M2 is at least one dopant other than Al; and when M1 is both Mn and Al, M2 is at least one dopant other than both Mn and Al.
[0061] Furthermore, the lithium composite oxide represented by the above chemical formula 1 can be a high-nickel lithium composite oxide with a Ni content of 50% or more, preferably 60% or more, and more preferably 80% or more. The Ni content in the above lithium composite oxide can be calculated by the following formula 1, and can be represented by "1-(x+y+z)" in the above chemical formula 1. For example, when the above lithium composite oxide is a lithium composite oxide represented by NCM811, "1-(x+y+z)" in the above chemical formula 1 is 0.80.
[0062] [Formula 1]
[0063] Ni content = [Ni (mol%) / Ni (mol%) + Co (mol%) + M1 (mol%) + M2 (mol%)] × 100
[0064] The aforementioned positive electrode active material may include secondary particles formed by agglomerating multiple of the aforementioned lithium composite oxides, which are primary particles.
[0065] Here, a primary particle refers to a single grain (or crystallite), and a secondary particle refers to an aggregate formed by the aggregation of multiple primary particles. The primary particles can have rod-shaped, elliptical, and / or irregular shapes. Voids and / or grain boundaries may exist between the primary particles constituting the secondary particles.
[0066] For example, the primary particles can be spaced apart from adjacent primary particles within the secondary particles to form internal voids. Furthermore, the primary particles can form surfaces existing within the secondary particles by contacting these internal voids, rather than forming grain boundaries by contacting adjacent primary particles. On the other hand, the surfaces of the primary particles existing on the outermost surface of the secondary particles, exposed to external air, form the surface of the secondary particles.
[0067] The average major axis length of the primary particles is 0.1 μm to 5 μm, preferably 0.1 μm to 2 μm, thereby achieving the optimal density of the positive electrode prepared using the positive electrode active material according to various embodiments of the present invention. Furthermore, the average particle size of the secondary particles varies depending on the number of aggregated primary particles, but can be from 1 μm to 30 μm.
[0068] On the other hand, the lithium composite oxide contained in the positive electrode active material according to an embodiment of the present invention has a stepped structure on its surface. In this case, the stepped structure may exist on the surface of the primary particles and / or the secondary particles, more preferably, it may exist on the surface of the secondary particles.
[0069] The stepped structure formed on the surface of the lithium composite oxide does not simply refer to the voids present on the surface of the lithium composite oxide or the curvature of the surface formed by the aggregation of multiple lithium composite oxides, but should be understood as a stepped structure formed on the entire surface of the primary particles and / or the secondary particles.
[0070] The aforementioned stepped structure can also be defined as a terrace-step structure. In this case, the terrace-step structure may further include a kink structure.
[0071] Figure 1 The illustration schematically shows the process of introducing a stepped structure into the surface portion of a lithium composite oxide contained in a positive electrode active material according to an embodiment of the present invention.
[0072] The aforementioned stepped structure is a structure formed by stacking multiple planes that are horizontal or nearly horizontal relative to the surface of the primary particles and / or the secondary particles. The plane area gradually decreases from the portion relatively close to the surface of the primary particles and / or the secondary particles toward the portion far away from the surface of the primary particles and / or the secondary particles, thereby forming a stepped structure from the stacking of multiple planes.
[0073] Reference Figure 1The platform t and the step s that constitute the above-mentioned stepped structure can be repeated periodically. Compared with the surface area of the platform t near the surface of the primary particle and / or the secondary particle, the surface area of the platform t far from the surface is smaller, thereby forming the above-mentioned stepped structure on the surface of the primary particle and / or the secondary particle.
[0074] That is, as the aforementioned platform t and the aforementioned step s are periodically repeated, a structure approaching a so-called step shape may exist on the surface of the primary particles and / or the secondary particles. The direction in which the aforementioned platform t and the aforementioned step s are periodically repeated on the surface of the primary particles and / or the aforementioned secondary particles may be along the long axis and short axis of the aforementioned lithium composite oxide, or it may be non-directional.
[0075] In addition, such as Figure 1 As shown, the aforementioned step structure may also include a kink structure. The kink refers to the recessed or protruding area of the platform t and / or the step s in the platform-step structure. The location and direction of the kink forming on the platform t and / or the step s may also be non-directional.
[0076] The aforementioned step structure can help to simultaneously improve electrochemical properties and stability, which have a trade-off relationship, or improve stability while at least minimizing the reduction in electrochemical properties, or improve electrochemical properties while minimizing the reduction in stability.
[0077] In the following text, the orientation of the aforementioned step structure formed on the surface of the aforementioned lithium composite oxide will be explained together with the crystal structure of the aforementioned lithium composite oxide.
[0078] Refer to the TEM image shown, which depicts the surface portion of a lithium complex oxide contained in a positive electrode active material according to one embodiment. Figure 12 The stepped structure formed on the surface of the primary particles and / or the secondary particles can be formed to intersect with the extension direction of the (003) crystal plane of the lithium composite oxide.
[0079] The (003) crystal plane is a specific crystal plane of the lithium composite oxide and is formed in one direction inside the lithium composite oxide. Therefore, the step structure existing on the surface of the lithium composite oxide is formed to intersect with the extension direction of the (003) crystal plane.
[0080] At this time, the step structure being formed to intersect with the extension direction of the (003) crystal plane means that the step structure exists at least in a direction perpendicular or nearly perpendicular to the extension direction of the (003) crystal plane.
[0081] As described above, since the stepped structure is formed to intersect with the extension direction of the (003) crystal plane of the lithium composite oxide, it can help improve the diffusion ability of lithium ions through the lithium composite oxide.
[0082] Furthermore, the stepped structure formed on the surface portion of the lithium composite oxide can be formed along the extension direction of a crystal plane belonging to at least one family of planes selected from the {01x}, {02y}, and {03z} plane families present on the surface portion of the lithium composite oxide, or along a plane parallel or nearly parallel to the extension direction (where x, y, and z are each independently an integer from 0 to 12).
[0083] At this time, the formation of the above-mentioned step structure along the extension direction of a specific crystal plane means that the platform-step of the above-mentioned step structure is formed along the extension direction of a specific crystal plane formed on the surface of the above-mentioned lithium composite oxide, or is formed such that the dihedral angle formed relative to the extension direction of the specific crystal plane is 90° or more.
[0084] In other words, the aforementioned step structure can be formed such that any crystal plane belonging to at least one of the plane families selected from {01x}, {02y}, and {03z} in the surface portion of the lithium composite oxide has a predetermined dihedral angle with an adjacent crystal plane. In this case, the dihedral angle between any crystal plane belonging to at least one of the plane families selected from {01x}, {02y}, and {03z} and an adjacent crystal plane can be 90° or more.
[0085] For example, crystal planes belonging to the {01x} family include (011), (012), and (014) crystal planes, crystal planes belonging to the {02y} family include (021) and (022) crystal planes, and crystal planes belonging to the {03z} family include (003) and (030) crystal planes.
[0086] For reference, even planar families and crystal planes not specifically specified herein can form the stepped structures defined herein on the surface of the aforementioned lithium composite oxides.
[0087] On the other hand, the step structure formed on the surface of the lithium composite oxide can have a periodically repeating shape. Specifically, the step structure having a predetermined dihedral angle with at least one crystal plane selected from the {01x}, {02y} and {03z} planar families of the lithium composite oxide can be formed as a periodic repeating shape (where x, y and z are each independently an integer from 0 to 12).
[0088] Similarly, even for planar families and crystal planes not specifically specified herein, the aforementioned step structure can be formed by periodically repeating a step structure having a predetermined dihedral angle between the planar families and crystal planes mainly formed on the surface portion of the aforementioned lithium composite oxide.
[0089] The lithium-ion diffusion path in the lithium composite oxide constituting the positive electrode active material is formed in a direction parallel to the extension direction of the (003) crystal plane. At the same time, when the lithium-ion diffusion path is directed toward the (012), (014), and (022) crystal planes, which are relatively free for the diffusion and desorption of lithium ions from the inside to the outside of the lithium composite oxide, it is expected to improve the electrochemical characteristics of the positive electrode active material including the lithium composite oxide.
[0090] On the other hand, the aforementioned stepped structure can become a non-directional topography independent of the directionality of the crystal planes measured from the interior and surface of the aforementioned lithium composite oxide.
[0091] In another embodiment, a coating comprising an oxide represented by the following chemical formula 2 is formed on at least a portion of the surface of the primary particles and / or the secondary particles.
[0092] [Chemical Formula 2]
[0093] Li a M3 b O c
[0094] (Where M3 is selected from at least one of Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Gd, and Nd, 0≤a≤8, 0 <b≤8,2≤c≤13)
[0095] The coating is selectively present on at least a portion of the surface of the primary particles and / or the secondary particles, and the coating can be defined as a region on the surface of the primary particles and / or the secondary particles in which the oxide represented by the above chemical formula 2 is present.
[0096] The coating may continuously or discontinuously cover at least a portion of the surface of the primary particles and / or the secondary particles. When the coating is discontinuous, it may exist in the form of islands. Alternatively, the coating may exist as a solid solution that does not form a boundary with the primary particles and / or the secondary particles, but is not limited thereto.
[0097] On the other hand, even if the above-mentioned coating is present on the surface of the lithium composite oxide, it is preferable that the stepped structure present on the surface of the lithium composite oxide remains unchanged.
[0098] If the coating is present on the surface of the lithium composite oxide, the coating may also include a surface portion having a stepped structure. In this case, the stepped structure will conform to the stepped structure present in the surface portion of the lithium composite oxide.
[0099] Similarly, when the stepped structure present on the surface of the lithium composite oxide is a platform stepped bent structure that also includes a bent structure, the surface of the coating will also have a platform stepped bent structure.
[0100] On the other hand, at least one of the oxides contained in the above coating may be a boron-containing oxide such as a borate-based compound or an LBO (lithium borate)-based compound, which may be represented by the following chemical formula 3.
[0101] [Chemical Formula 3]
[0102] Li d B e O f
[0103] (where 0≤d≤8,0) <e≤8,2≤f≤13)
[0104] Non-limiting examples of the aforementioned boron-containing oxides include B2O3, Li2O-B2O3, LiBO2, Li3BO3, Li3BO5, Li2B4O7, Li2B2O7, and Li2B8O. 13 Li6B4O9, etc.
[0105] The aforementioned boron-containing oxide can provide surface protection for the aforementioned lithium composite oxide to suppress surface side reactions, thereby improving the stability of the positive electrode active material. The coating further includes additional oxides besides the boron-containing oxide, which not only reduce lithium-containing impurities on the surface of the aforementioned lithium composite oxide but also serve as a diffusion path for lithium ions, thereby improving the electrochemical characteristics of the aforementioned positive electrode active material.
[0106] The aforementioned oxide can be an oxide formed by complexing lithium with an element represented by M3, or an oxide of M3, for example, the aforementioned oxide can be Li. a W b O c Li a Zr b O c Li aTi b O c Li a Ni b O c Li a Co b O c Li a Al b O c Co b O c Al b O c W b O c Z r b O c or Ti b O c However, the examples above are only for ease of understanding, and the oxides defined herein are not limited to the examples above.
[0107] Furthermore, the aforementioned oxide can be an oxide composed of lithium and at least two elements represented by M3, or further includes an oxide composed of lithium and at least two elements represented by M3. For example, an oxide composed of lithium and at least two elements represented by M3 can be Li a (W / Ti) b O c Li a (W / Zr) b O c Li a (W / Ti / Zr) b O c Li a (W / Ti / B) b O c And so on, but not limited to these.
[0108] Lithium secondary batteries
[0109] According to another embodiment of the present invention, the present invention can provide a positive electrode comprising a positive current collector and a positive active material layer formed on the positive current collector. The positive active material layer may comprise a lithium composite oxide as the positive active material according to various embodiments of the present invention. Therefore, the lithium composite oxide is the same as described above, and for convenience, its specific description will be omitted. Hereinafter, only the remaining undescribed components will be described. Furthermore, for convenience, the lithium composite oxide will be referred to as the positive active material below.
[0110] There are no particular limitations on the aforementioned positive electrode current collector, as long as it does not induce chemical changes in the battery and is conductive. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surfaces treated with carbon, nickel, titanium, silver, etc., can be used. Furthermore, the aforementioned positive electrode current collector typically has a thickness of 3μm to 500μm, and fine irregularities can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, it can be used in various forms such as thin films, sheets, foils, meshes, porous bodies, foams, and nonwovens.
[0111] The aforementioned positive electrode active material layer can be prepared by coating the aforementioned positive electrode current collector with a positive electrode slurry composition comprising the aforementioned positive electrode active material, a conductive material, and, if desired, a binder.
[0112] In this case, the content of the positive electrode active material relative to the total weight of the positive electrode active material layer can be from 80% to 99% by weight, more specifically from 85% to 98.5% by weight. When the positive electrode active material is included in the above content range, excellent capacity characteristics can be exhibited, but it is not limited thereto.
[0113] The aforementioned conductive materials are used to impart conductivity to the electrodes. In the constructed battery, they can be used without restriction as long as they do not cause chemical changes and possess electronic conductivity. Specific examples include graphite such as natural or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. One or more mixtures of these materials may be used. The total weight of the positive electrode active material layer may range from 0.1% to 15% by weight of the aforementioned conductive materials.
[0114] The aforementioned binder enhances the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), ethylene-vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated ethylene propylene diene monomer (EPDM), styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof; one or more mixtures thereof may be used. The binder may comprise 0.1% to 15% by weight of the aforementioned binder relative to the total weight of the positive electrode active material layer.
[0115] In addition to utilizing the aforementioned positive electrode active material, the positive electrode can be prepared according to conventional positive electrode preparation methods. Specifically, it can be prepared by coating a positive electrode slurry composition onto a positive electrode current collector and then drying and calendering it. The positive electrode slurry composition is prepared by dissolving or dispersing the aforementioned positive electrode active material in a solvent and selectively dissolving or dispersing the binder and conductive material in the solvent.
[0116] The solvents mentioned above can be solvents commonly used in this technical field, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or a mixture of two or more of them can be used. Considering the coating thickness and preparation yield of the slurry, the amount of the solvent used should be sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to have a viscosity that exhibits excellent thickness uniformity when coated for the preparation of the positive electrode.
[0117] Furthermore, in another embodiment, the positive electrode can also be prepared by casting the positive electrode slurry composition onto a separate support, and then laminating the thin film obtained by peeling off the support onto the positive electrode current collector.
[0118] Meanwhile, according to another embodiment of the present invention, an electrochemical device including the above-described positive electrode can be provided. Specifically, the electrochemical device is a battery, a capacitor, etc., and more specifically, a lithium secondary battery.
[0119] Specifically, the aforementioned lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separator and electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as described above; therefore, for convenience, a detailed description is omitted. The remaining components not previously described will be explained below.
[0120] The aforementioned lithium secondary battery may optionally include: a battery container for housing the electrode assembly comprising the positive electrode, the negative electrode, and the separation membrane; and a sealing component for sealing the battery container.
[0121] The aforementioned negative electrode may include a negative current collector and a layer of negative active material located on the aforementioned negative current collector.
[0122] There are no particular limitations on the aforementioned negative electrode current collector, as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surfaces treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloys can be used. Furthermore, the aforementioned negative electrode current collector can typically have a thickness of 3μm to 500μm. Similar to the positive electrode current collector, the bonding force of the negative electrode active material can be enhanced by forming fine irregularities on the surface of the current collector. For example, it can be used in various forms such as thin films, sheets, foils, meshes, porous bodies, foams, and nonwovens.
[0123] The aforementioned negative electrode active material layer can be prepared by coating the aforementioned negative electrode current collector with a negative electrode slurry composition comprising the aforementioned negative electrode active material and conductive material, and selectively including a binder as needed.
[0124] As the aforementioned negative electrode active material, compounds capable of reversible lithium insertion and extraction can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; and metal compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; such as SiO₂. β Metal oxides capable of being doped and dedoped with lithium, such as (0 < β < 2), SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the above-mentioned metal compounds and carbon materials, such as Si-C composites or Sn-C composites, may be used, and one or more mixtures thereof may be used. Furthermore, lithium metal films may also be used as the above-mentioned negative electrode active material. Moreover, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, while representative high-crystalline carbons are amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitch, and high-temperature calcined carbons such as petroleum or coal tar pitch-derived cokes.
[0125] Based on the total weight of the negative electrode active material layer, it may contain 80% to 99% of the aforementioned negative electrode active material.
[0126] The aforementioned binder is a component that facilitates the bonding between the conductive material, the active material, and the current collector. Typically, based on the total weight of the negative electrode active material layer, 0.1% to 10% of the aforementioned binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0127] The aforementioned conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, up to 10% by weight of the aforementioned conductive material can be added, preferably up to 5% by weight. There are no particular limitations on this conductive material as long as it does not induce chemical changes in the corresponding battery and has conductivity. For example, graphite such as natural graphite or artificial graphite can be used; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber or metal fiber; metal powders such as fluorinated carbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0128] In one embodiment, the aforementioned negative electrode active material layer can be prepared by coating a negative electrode slurry composition onto a negative electrode current collector and drying it. The negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing the binder and conductive material in the solvent. Alternatively, the negative electrode slurry composition can be cast onto a separate support, and then a thin film layer obtained by peeling off the support can be pressed onto the negative electrode current collector.
[0129] Furthermore, in another embodiment, the aforementioned negative electrode active material layer can also be prepared by coating a negative electrode slurry composition onto a negative electrode current collector and drying it. The aforementioned negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing the binder and conductive material in the solvent. Alternatively, the aforementioned negative electrode slurry composition can be cast onto a separate support, and then a thin film layer obtained by peeling off the support can be pressed onto the negative electrode current collector.
[0130] Furthermore, in the aforementioned lithium secondary battery, the separator membrane is used to separate the negative and positive electrodes and provide a channel for lithium ion movement. Any separator membrane commonly used in lithium secondary batteries can be used without limitation. In particular, it is preferable to have low impedance and excellent electrolyte moisture-holding capacity for electrolyte ion movement. Specifically, porous polymer films can be used, for example, porous polymer films prepared from polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or laminated structures of two or more layers thereof. Furthermore, conventional porous nonwoven fabrics can also be used, for example, nonwoven fabrics made from high-melting-point glass fibers, polyethylene terephthalate fibers, etc. Moreover, to ensure heat resistance or mechanical strength, separator membranes coated with ceramic components and polymeric substances can also be used, selectively in single-layer or multi-layer structures.
[0131] Furthermore, examples of electrolytes used in this invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes, but they are not limited to these.
[0132] Specifically, the electrolyte may contain organic solvents and lithium salts.
[0133] As the aforementioned organic solvents, organic solvents that can act as a medium for the movement of ions participating in the electrochemical reaction of the battery can be used without limitation. Specifically, as the aforementioned organic solvents, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorinated benzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methylethyl carbonate (MEC), ethylmethyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (EPC) can be used. Carbonate solvents such as ate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (where r is a straight-chain, branched, or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain double bonds, aromatic rings, or ether bonds); amides such as dimethylformamide; dioxanes such as 1,3-dioxane; or sulfolane. Among these, carbonate solvents are preferred, and more preferably, mixtures of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) and low-viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) with high ionic conductivity and high dielectric constant, which can improve the charge-discharge performance of the battery, are more suitable. In this case, when the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance is observed.
[0134] The lithium salts described above can be any compound capable of providing lithium ions for use in lithium secondary batteries. Specifically, the lithium salts can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2, etc. Preferably, the concentration of the lithium salts is in the range of 0.1M to 2.0M. If the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, thus exhibiting excellent electrolyte performance and enabling efficient movement of lithium ions.
[0135] In addition to the electrolyte components described above, for the purpose of improving battery life characteristics, suppressing battery capacity reduction, and increasing battery discharge capacity, the electrolyte may also contain one or more additives such as halogenated alkylene carbonate compounds like difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, triammonium hexaphosphate, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolides, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol, or aluminum trichloride. In this case, the electrolyte may contain 0.1% to 5% of the aforementioned additives relative to its total weight.
[0136] As described above, lithium secondary batteries containing the positive electrode active material of the present invention stably exhibit excellent discharge capacity, output characteristics, and lifespan characteristics. Therefore, they can be used in portable devices such as mobile phones, laptops, and digital cameras, as well as in electric vehicles such as hybrid electric vehicles (HEVs).
[0137] The lithium secondary battery of the present invention is not particularly limited in shape and can be cylindrical, prismatic, pouch-shaped, or coin-shaped, etc. Furthermore, preferably, the lithium secondary battery can be used not only as a single battery cell for powering small devices, but also as a unit battery in medium or large battery modules comprising multiple battery cells.
[0138] According to another embodiment of the present invention, a battery module comprising the above-mentioned lithium secondary battery as a single unit and / or a battery pack comprising the same can be provided.
[0139] The aforementioned battery module or battery pack can be used as a power tool; an electric vehicle, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); or a power source for one or more medium or large-sized devices in an energy storage system.
[0140] Preparation Example 1. Preparation of Positive Electrode Active Material
[0141] Example 1
[0142] Ni was prepared using a precursor aqueous solution prepared by mixing nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of 98:1:1. 0.98 Co 0.01 Mn 0.01 Nickel complex precursor of (OH)2.
[0143] The above nickel composite precursor was mixed with LiOH (Li / metal ratio = 1.06), and then calcined for 10 hours at a rate of 2°C per minute to 790°C while maintaining an O2 atmosphere in the calcining furnace. The mixture was then decomposed to obtain lithium composite oxide.
[0144] Next, the lithium composite oxide was washed with distilled water containing 3 mol% Co(OH)2, and then filtered and dried.
[0145] Then, the dried lithium composite oxide was mixed with LiOH and H3BO3, and then calcined for 10 hours at 720°C at a rate of 4°C per minute while maintaining an O2 atmosphere in the calcination furnace. After natural cooling, the positive electrode active material was obtained as the final product.
[0146] Before the second firing, the mixture is prepared such that the total composition contains 4 mol% LiOH and 0.1 mol% H3BO3.
[0147] Example 2
[0148] Except for mixing prior to the second firing to achieve an H3BO3 content of 0.3 mol% in the total composition, the positive electrode active material was prepared in the same manner as in Example 1.
[0149] Comparative Example 1
[0150] Except for mixing the lithium composite oxide with LiOH instead of mixing the lithium composite oxide with LiOH and H3BO3 before the second firing, the positive electrode active material was prepared in the same manner as in Example 1. Mixing was performed before the second firing such that the LiOH content in the total composition was 4 mol%.
[0151] Example 3
[0152] Ni was prepared using a precursor aqueous solution of nickel sulfate and cobalt sulfate mixed in a molar ratio of 96.0:4.0. 0.96 Co 0.04 Nickel complex precursor of (OH)2.
[0153] The above nickel composite precursor, LiOH (Li / metal ratio = 1.04) and 1.4 mol% Al(OH)3 were mixed and then calcined in a furnace with an O2 atmosphere, at a temperature of 2°C per minute to 720°C for 10 hours. The mixture was then decomposed to obtain lithium composite oxide.
[0154] Next, the lithium composite oxide was washed with distilled water containing 3 mol% Co(OH)2, and then filtered and dried.
[0155] Then, the dried lithium composite oxide was mixed with LiOH and H3BO3, and then calcined for 10 hours at 720°C at a rate of 4°C per minute while maintaining an O2 atmosphere in the calcination furnace. After natural cooling, the positive electrode active material was obtained as the final product.
[0156] Before the second firing, the mixture is prepared such that the total composition contains 5 mol% LiOH and 0.25 mol% H3BO3.
[0157] Comparative Example 2
[0158] Except for mixing the lithium composite oxide with LiOH instead of mixing the lithium composite oxide with LiOH and H3BO3 before the second firing, the positive electrode active material was prepared in the same manner as in Example 3. Mixing was performed before the second firing such that the LiOH content in the total composition was 5 mol%.
[0159] Example 4
[0160] Ni was prepared using a precursor aqueous solution of nickel sulfate and cobalt sulfate mixed in a molar ratio of 92.0:8.0. 0.92 Co 0.08 Nickel complex precursor of (OH)2.
[0161] The above nickel composite precursor, LiOH (Li / metal ratio = 1.04) and 1.4 mol% Al(OH)3 were mixed and calcined in a furnace with an O2 atmosphere, at a temperature of 2°C per minute to 750°C for 10 hours. The mixture was then decomposed to obtain lithium composite oxide.
[0162] Then, the lithium composite oxide, LiOH, Co3O4 and H3BO3 were mixed and calcined in a furnace with an O2 atmosphere, and the temperature was increased to 720°C at a rate of 4°C per minute for 10 hours. After natural cooling, the positive electrode active material was obtained as the final product.
[0163] Before the second firing, the mixture is prepared such that the total composition contains 4 mol% LiOH, 3 mol% Co3O4, and 0.25 mol% H3BO3.
[0164] Comparative Example 3
[0165] Except for the mixing of lithium composite oxide, LiOH, and H3BO3 instead of mixed lithium composite oxide, LiOH, Co3O4, and H3BO3 before the second firing, the positive electrode active material was prepared in the same manner as in Example 4.
[0166] Comparative Example 4
[0167] Except for mixing lithium composite oxide, LiOH, and Co3O4 instead of mixed lithium composite oxide, LiOH, Co3O4, and H3BO3 before the second firing, the positive electrode active material was prepared in the same manner as in Example 4.
[0168] Example 5
[0169] Ni was prepared using a precursor aqueous solution of nickel sulfate and cobalt sulfate mixed in a molar ratio of 92.0:8.0. 0.92 Co 0.08 Nickel complex precursor of (OH)2.
[0170] The above nickel composite precursor, LiOH (Li / metal ratio = 1.04) and 1.4 mol% Al(OH)3 were mixed and calcined in a furnace with an O2 atmosphere, at a temperature of 2°C per minute to 750°C for 10 hours. The mixture was then decomposed to obtain lithium composite oxide.
[0171] Then, the lithium composite oxide, Co3O4 and H3BO3 were mixed and calcined in a furnace with an O2 atmosphere, and the temperature was increased to 720°C at a rate of 4°C per minute for 10 hours. After natural cooling, the positive electrode active material was obtained as the final product.
[0172] Before the second firing, the mixture is prepared such that the total composition contains 3 mol% Co3O4 and 0.25 mol% H3BO3.
[0173] Comparative Example 5
[0174] Except for mixing lithium composite oxide and H3BO3 instead of mixed lithium composite oxide, Co3O4 and H3BO3 before the second firing, the positive electrode active material was prepared in the same manner as in Example 5.
[0175] Comparative Example 6
[0176] Except for mixing lithium composite oxide and Co3O4 instead of mixed lithium composite oxide, Co3O4 and H3BO3 before the second firing, the positive electrode active material was prepared in the same manner as in Example 5.
[0177] Preparation Example 2. Preparation of Lithium Secondary Batteries
[0178] A positive electrode slurry was prepared by dispersing 94% by weight of each of the positive electrode active materials prepared according to Preparation Example 1, 3% by weight of artificial graphite, and 3% by weight of PVDF binder in 3.5 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was then uniformly coated onto a 20 μm thick aluminum film serving as the positive electrode current collector and dried. The film was then rolled to prepare the positive electrode. The positive electrode loading level was 7 mg / cm³. 2 The electrode density is 3.2 g / cm³. 3 .
[0179] In contrast to the aforementioned positive electrode, lithium foil was used as the counter electrode, and a porous polyethylene membrane (Celgard 2300, thickness: 25 μm) was used as the separation membrane. A button cell was prepared using a liquid electrolyte containing ethylene carbonate and ethyl methyl carbonate in a 3:7 volume ratio and LiPF6 at a concentration of 1.15 M through a conventional preparation process.
[0180] Experimental Example 1. Structural Analysis of Positive Electrode Active Material
[0181] (1) Cross-sectional SEM analysis of the positive electrode active material
[0182] SEM images of the lithium composite oxide contained in the positive electrode active material prepared according to Preparation Example 1 were obtained using an FE-SEM device.
[0183] Figure 2 and Figure 3SEM images of the surface portion of the lithium composite oxide contained in the positive electrode active material according to Example 1 and Comparative Example 1 were taken respectively. Figure 4 and Figure 5 SEM images of the surface portion of the lithium composite oxide contained in the positive electrode active material according to Example 3 and Comparative Example 2 were taken respectively. Figures 6 to 8 SEM images of the surface of the lithium composite oxide contained in the positive electrode active materials of Example 4, Comparative Example 3, and Comparative Example 4 were taken, respectively. Figures 9 to 11 SEM images of the surface portion of the lithium composite oxide contained in the positive electrode active material according to Example 5, Comparative Example 5 and Comparative Example 6 were taken.
[0184] In summary, it can be seen that a stepped structure is introduced into the surface portion of the lithium composite oxide contained in the positive electrode active material according to Examples 1 to 5. Furthermore, it can be confirmed that the stepped structure introduced into the surface portion of the lithium composite oxide is not simply caused by the bending of primary particles present on the surface portion of secondary particles.
[0185] The stepped structure introduced on the surface of the lithium composite oxide contained in the positive electrode active material of Examples 1 to 5 can also be regarded as a platform step structure, and it can be confirmed that a partially formed bent platform step structure is formed.
[0186] On the other hand, it can be confirmed that there is almost no step structure on the surface of the lithium composite oxide contained in the positive electrode active material according to Comparative Examples 1 to 6.
[0187] (2) TEM analysis of positive electrode active material
[0188] After obtaining a TEM image of the lithium composite oxide contained in the positive electrode active material according to Example 1 in Preparation Example 1, the direction of the lithium ion diffusion path formed in the lithium composite oxide was confirmed from the TEM image.
[0189] Furthermore, by indexing the diffraction patterns obtained from the fast Fourier transform (FFT) of the HR-TEM images, the crystal planes of the lithium composite oxides in which the lithium ion diffusion paths formed in the aforementioned lithium composite oxides are oriented were confirmed.
[0190] Figure 12 To capture a TEM image of the surface portion of the lithium composite oxide contained in the positive electrode active material according to Example 1, each crystal facet constituting the surface portion of the lithium composite oxide is shown.
[0191] Reference Figure 12It can be confirmed that the step structure formed on the surface of the lithium composite oxide contained in the positive electrode active material according to Example 1 is a step structure that belongs to a specific crystal plane selected from the {01x}, {02y} and {03z} family and has a dihedral angle of more than 90 degrees between adjacent crystal planes.
[0192] Furthermore, the lithium-ion diffusion path in the lithium composite oxide constituting the positive electrode active material is formed in a direction parallel to the extension direction of the (003) crystal plane. At the same time, when the lithium-ion diffusion path is directed toward the (012), (014), and (022) crystal planes, which are relatively free for the diffusion and desorption of lithium ions from the inside to the outside of the lithium composite oxide, it is expected to improve the electrochemical characteristics of the positive electrode active material including the lithium composite oxide.
[0193] (3) Surface coating analysis
[0194] XPS analysis was performed on the positive electrode active material according to Example 1 to analyze the composition of the surface portion of the lithium composite oxide. The XPS analysis was performed using a Quantum 2000 (Physical Electronics, Inc., accelerating voltage: 0.5 keV to 15 keV, 300 W, energy resolution: approximately 1.0 eV, minimum analytical area: 10 μm, sputtering rate: 0.1 nm / min).
[0195] Figure 13 To illustrate the XPS depth profile of the lithium composite oxide contained in the positive electrode active material according to Example 1, refer to... Figure 13 It can be confirmed that boron (B) was detected only on the outermost surface of the aforementioned lithium composite oxide (secondary particles).
[0196] Reference as shown in Figure 13 A graph of the B1s XPS spectra of regions where boron (B) was detected in XPS depth profiling. Figure 14 A characteristic B1s peak of lithium borate was detected in the region of approximately 191.4 eV.
[0197] Additionally, referring to the interplanar spacing of the crystal planes of regions A and B in the TEM image of the lithium composite oxide contained in the positive electrode active material according to Example 1,... Figure 15 In region A, the interplanar spacing equivalent to the (003) crystal plane of a typical NCA or NCM type lithium composite oxide can be measured.
[0198] On the other hand, in region B corresponding to the outermost surface of the aforementioned lithium composite oxide, an interplanar spacing different from that in region A (i.e., the (003) crystal plane) can be measured. The interplanar spacing.
[0199] Depend on Figure 13 and Figure 14 The results confirm the presence of any boron-containing oxide on the outermost surface of the aforementioned lithium composite oxide. In this case, the interplanar spacing of the boron-containing oxide is approximately... The compounds are LiBO2, Li3BO5 and Li2B4O7. Therefore, it can be predicted that LiBO2, Li3BO5 and / or Li2B4O7 are present on the outermost surface of the above lithium composite oxide.
[0200] On the other hand, the same experiment was performed on the positive electrode active materials according to Examples 2 to 5, and it was confirmed that a coating containing lithium borate was formed on the outermost surface of the lithium composite oxide contained in the above positive electrode active materials.
[0201] Experimental Example 2. Evaluation of the Electrochemical Characteristics of Lithium Secondary Batteries
[0202] The discharge capacity and charge / discharge efficiency of the lithium secondary battery (button cell) prepared according to Preparation Example 2 were determined by performing charge / discharge experiments under conditions of 25°C, a voltage range of 3.0V to 4.3V, and a discharge rate of 0.1C to 5.0C.
[0203] In addition, the same lithium secondary battery was subjected to 50 charge / discharge cycles at 1C / 1C conditions within a driving voltage range of 3.0V to 4.4V at 25°C, and the ratio of the discharge capacity at the 50th cycle to the initial capacity was then measured (capacity retention).
[0204] The results of the above measurements are shown in Table 1 below.
[0205] Table 1
[0206]
[0207] Referring to the results in Table 1 above, and referring to the results of the corresponding embodiments and comparative examples, it can be confirmed that the charge-discharge efficiency and cycle capacity retention of the embodiment using a positive electrode active material containing a lithium composite oxide with a stepped structure formed on the surface are generally higher than the charge-discharge efficiency and cycle capacity retention of the comparative examples.
[0208] While the embodiments of the present invention have been described above, those skilled in the art will understand that various modifications and alterations can be made to the present invention by adding, modifying, deleting, or supplementing the constituent elements without departing from the spirit of the present invention as described in the claims, and these modifications and alterations also fall within the scope of the present invention.
Claims
1. A positive electrode active material comprising a lithium composite oxide capable of lithium intercalation and deintercalation, characterized in that, The aforementioned lithium composite oxide includes a surface portion having a stepped structure. The aforementioned stepped structure is a platform-stepped, bent structure. The aforementioned platform-step bending structure is a structure formed by stacking multiple planes that are horizontal or nearly horizontal relative to the surface of the aforementioned lithium composite oxide. It includes a platform-step structure formed by stacking multiple planes with the planar area gradually decreasing from the portion relatively close to the surface to the portion far from the surface, and at least a portion of the aforementioned platform and the aforementioned steps being concave or protruding bends.
2. The positive electrode active material according to claim 1, characterized in that, The aforementioned lithium composite oxide contains at least nickel and cobalt.
3. The positive electrode active material according to claim 2, characterized in that, The aforementioned lithium composite oxide also contains at least one selected from manganese and aluminum.
4. The positive electrode active material according to claim 1, characterized in that, The stepped structure formed on the surface of the lithium composite oxide is configured to intersect with the extension direction of the (003) crystal plane of the lithium composite oxide.
5. The positive electrode active material according to claim 1, characterized in that, The step structure formed on the surface portion of the lithium composite oxide is formed such that any crystal plane in the surface portion of the lithium composite oxide belonging to at least one family of planes selected from the family of {01x}, {02y} and {03z} has a predetermined dihedral angle with an adjacent crystal plane, wherein x, y and z are each independently integers from 0 to 12.
6. The positive electrode active material according to claim 5, characterized in that, The dihedral angle between any crystal plane belonging to at least one of the plane families selected from {01x}, {02y} and {03z} and an adjacent crystal plane is 90° or more.
7. The positive electrode active material according to claim 5, characterized in that, On the surface portion of the aforementioned lithium composite oxide, a structure is formed in which any crystal plane belonging to at least one plane family selected from the {01x}, {02y}, and {03z} plane families in the surface portion of the aforementioned lithium composite oxide has a predetermined dihedral angle with an adjacent crystal plane, which is periodically repeated.
8. The positive electrode active material according to claim 1, characterized in that, The above-mentioned lithium composite oxide is represented by the following chemical formula 1: [Chemical Formula 1] The w Nor 1-(x+y+z) Co x M1 y M2 z O2 in, M1 is at least one selected from Mn and Al. M2 is selected from at least one of Mn, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, B, and Cu. M1 and M2 are distinct elements. 0.5≤w≤1.5, 0≤x≤0.50, 0 <y≤0.20,0≤z≤0.20。 9. The positive electrode active material according to claim 1, characterized in that, The aforementioned positive electrode active material includes secondary particles formed by agglomerating multiple of the aforementioned lithium composite oxides, which are primary particles. At least a portion of the surfaces of the primary particles and the secondary particles are formed with a coating comprising an oxide represented by the following chemical formula 2: [Chemical Formula 2] Read a M3 b Oh c in, M3 is selected from at least one of Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Gd, and Nd. 0≤a≤8,0 <b≤8,2≤c≤13。 10. The positive electrode active material according to claim 9, characterized in that, The aforementioned oxides include at least one boron-containing oxide represented by the following chemical formula 3: [Chemical Formula 3] Li d B e O f in, 0≤d≤8,0 <e≤8,2≤f≤13。 11. A positive electrode, characterized in that, include: Positive current collector; and A positive electrode active material layer is formed on the positive electrode current collector and includes the positive electrode active material as described in any one of claims 1 to 10.
12. A lithium secondary battery, characterized in that, Use the positive electrode as described in claim 11.
Citation Information
Patent Citations
Cathode active material, method for preparing the same, and lithium secondary batteries comprising the same
KR1020150069334A
Positive active material for rechargeable lithium battery and method of preparing the same, and rechargeable lithium battery including the same
CN111864194A
Non-aqueous electrolyte secondary battery
US20210075013A1